Analysis of Speech Acts of Ustadz Adi Hidayat's Lecture on Success and Happiness: A Study of Locutionary, Illocutionary, and Perlocutionary Acts - Rangkuti, Alpan Noor Habib; Supriadi, Rinaldi; Farisi, Mohamad Zaka Al; Sambo, Faisal Hamdani (Bahasa Indonesia Prima, 2025)
This study aims to analyze the forms of speech acts in Ustadz Adi Hidayat's lecture entitled